Clinical exome sequencing in the diagnosis of pediatric neuromuscular disease. Issue 3 (13th November 2020) - Herman, Isabella; Lopez, Michael A.; Marafi, Dana; Pehlivan, Davut; Calame, Daniel G.; Abid, Farida; Lotze, Timothy E.
Abstract: Background: The diagnosis of uncommon pediatric neuromuscular disease (NMD) is challenging due to genetic and phenotypic heterogeneity, yet is important to guide treatment, prognosis, and recurrence risk. Patients with diagnostically challenging presentations typically undergo extensive testing with variable molecular diagnostic yield. Given the advancement in next generation sequencing (NGS), we investigated the value of clinical whole exome sequencing (ES) in uncommon pediatric NMD. Methods: A retrospective cohort study of 106 pediatric NMD patients with a combination of ES, chromosomal microarray (CMA), and candidate gene testing was completed at a large tertiary referral center. Results: A molecular diagnosis was achieved in 37/79 (46%) patients with ES, 4/44 (9%) patients with CMA, and 15/74 (20%) patients with candidate gene testing. In 2/79 (3%) patients, a dual molecular diagnosis explaining the neuromuscular disease process was identified. A total of 42 patients (53%) who received ES remained without a molecular diagnosis at the conclusion of the study. Conclusions: Due to NGS, molecular diagnostic yield of rare neurological diseases is at an all‐time high. We show that ES has a higher diagnostic rate compared to other genetic tests in a complex pediatric neuromuscular disease cohort and should be considered early in the diagnostic journey for select NMD patients with challenging presentations in which a clinical diagnosis is not evident. Abstract : See Editorial on pages 282–284 in this issue .